2017
DOI: 10.2337/dc16-2113
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Postoperative Endogenous GLP-1 Levels Mediate Effects of Roux-en-Y Gastric Bypass on Neural Responsivity to Food Cues

Abstract: OBJECTIVEIt has been suggested that weight reduction and improvements in satiety after Rouxen-Y gastric bypass (RYGB) are partly mediated via postoperative neuroendocrine changes. Glucagon-like peptide-1 (GLP-1) is a gut hormone secreted after food ingestion and is associated with appetite and weight reduction, mediated via effects on the central nervous system (CNS). Secretion of GLP-1 is greatly enhanced after RYGB. We hypothesized that postoperative elevated GLP-1 levels contribute to the improved satiety r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 39 publications
4
70
0
Order By: Relevance
“…By contrast, the insulinotropic effect of GLP-1 is better maintained in T2DM (5). Moreover, GLP-1 has a physiological role in slowing gastric emptying (6) and suppressing glucagon secretion (7) and energy intake (8). Accordingly, GLP-1 is more important than GIP in driving the incretin effect and GIGD in T2DM.…”
mentioning
confidence: 99%
“…By contrast, the insulinotropic effect of GLP-1 is better maintained in T2DM (5). Moreover, GLP-1 has a physiological role in slowing gastric emptying (6) and suppressing glucagon secretion (7) and energy intake (8). Accordingly, GLP-1 is more important than GIP in driving the incretin effect and GIGD in T2DM.…”
mentioning
confidence: 99%
“…Appetite ratings were minimally affected in response to intraduodenal fat infusion, with and without vildagliptin or exendin (9–39), despite differences in GLP‐1 signalling. Previous studies have shown that DPP‐4 inhibition and antagonism of GLP‐1 receptors are also associated with changes in plasma levels of PYY that tend to confound the effect of GLP‐1 on appetite and energy intake . Moreover, the participants with T2DM in the present study had a mean age of ~69 years, so that their appetite sensations are expected to be decreased …”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have shown that DPP-4 inhibition and antagonism of GLP-1 receptors are also associated with changes in plasma levels of PYY that tend to confound the effect of GLP-1 on appetite and energy intake. 44,45 Moreover, the participants with T2DM in the present study had a mean age of~69 years, so that their appetite sensations are expected to be decreased. 46 Several limitations should be noted in interpreting our findings.…”
Section: Discussionmentioning
confidence: 91%
“…The central nervous system, especially the hypothalamus, can control the central and peripheral energy homeostasis through neuropeptides and neurotransmitters [59]. Some studies have confirmed that changes in the nervous system can be significantly observed after RYGB [60][61][62]. Liver fat metabolism is regulated by not only humoral but also the nervous system.…”
Section: Discussionmentioning
confidence: 99%